KARAKTERISASI TOXOPLASMA GONDII ISOLAT INDONESIA - Sagung Chandra Yowani; Endang Kumolosasi; Marlia Singgih Wibowo (Jurnal Kimia (Journal of Chemistry), 2007)
Cathodic protection basically reduces the corrosion rate of a metallic structure by reducing its corrosionpotential, Toxoplasma gondii isolated from diaphragm of sheep at an abbatoir in Sukabumi, West Java had beencharacterized by Centre Research Institute for Animal Sciences. The characterization included study of morphologyby optical microscope, study of ultrastructure by transmission electron microscope, the study of the parasite growthin mice Mus musculus, and study of proteins of the parasite. The growth of parasite in mice had been studied usingtwo groups of mice i.e., normal group and immunosuppressed group. The number of parasites was comparedstatistically using student’ t-pair test. Results showed that dexamethasone at a dose of 5.2 mg/20 g body weight intraperitoneally to the immunosuppresed mice did not increase the number of extracelluler parasites in the peritonealfluid. The best parasite harvest time was on the 4th day after inoculation. Determination of parasite protein obtainedat 4 days after inoculation using sodium dodecyl sulphate polyacrylamide gel electrophoresis showed a dominantsurface protein of 42 kDa.